A Break with History : Fifteen Years of Inequality Reduction in Latin America - World Bank (World Bank, 2012)
In 2004 the World Bank released a regional report titled 'Inequality in Latin America: Breaking with History?' Analyzing data from the early 1990s to the early 2000s, a period in which many countries in the region were experiencing increasing inequality, this study raised the question of whether Latin America could reverse its historical pattern of high and persistent inequality. The report concluded that although not easy, breaking with history was more than ever possible in the region. An additional decade of data presented in this brief shows that it was possible, mainly due to changes in labor markets (including a reduction in educational inequality and the skill premia, and greater female labor force participation), a higher incidence of government transfers, and additional factors such as demographic changes. The decrease in inequality is driven mostly by improvements in labor income, particularly a reduction in skill premiums, reflecting improved access to education as well as other factors. In contrast to the recent Latin American trends, Asia is witnessing rising inequality, pushed up by China and India - where income has traditionally been more equal. However, inequality remains very high in Latin America, with levels significantly above other middle income countries. As Latin America enters a new decade, it does so knowing that inequality reduction is possible in the region.